The relationship of aptitudes, career choice, gender and selected family variables to career decisions of college freshmen at Widya Mandira Catholic University in Kupang-Indonesia. - Kristianus, Manek. (1989)
ABSTRACT see Upload (MT GUID & COUN 51 1989)